Public Stranger Violence—What Makes You Vulnerable?A Comparison of Perspectives From Young Adults and Industry Experts - Maxwell, Lucy (Journal of interpersonal violence, 2021)
The purpose of this study was to determine the situational and individual factors that influence vulnerability to public stranger violence (PSV) from the perspective of young adults and industry professionals. In total, 25 young adults aged between 18 and 29 years formed one sample and participated in one of four focus groups. The second sample consisted of 10 industry professionals with backgrounds in policing, corrections, and forensic psychology. Each professional participated in an individual semistructured interview. Both samples were asked questions regarding vulnerability and safety in public, where responses were analyzed using a thematic analysis. Multiple themes were identified and categorized into situational and individual factors associated with victimization. Situational factors referred to aspects of the environment that may influence vulnerability to PSV and included visibility, location, and level of support for potential victims. Individual factors referred to aspects about the person that may influence vulnerability to PSV and included unpredictability, ease of target, stereotypes, in-groups versus out-groups, distractions, and personality traits. Although both samples identified similar situational factors, young adults were found to be either unaware of individual factors identified by industry professionals as influencing vulnerability or at least misunderstood some of these factors. This is problematic as young adults may be basing their public behaviors on misinformation that may in fact increase, rather than decrease, vulnerability to PSV. The findings from this study have implications for the design of personal safety programs as well as community-based interventions to reduce vulnerability, the prevalence of PSV, and the negative outcomes associated with PSV, including anxiety and fear of crime.